Activities of the Lithuanian Mathematical Society in 2007–2010 - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2010)
The article gives a survey of activities of the Lithuanian Mathematical Society during the past three years. Some problems of the mathematical life in Lithuania are raised.